Análise do comportamento da Criosfera nos períodos do início do Holoceno e pré-industrial - Brito Neto, Francisco Agustinho de (Universidade Federal do Rio Grande do Norte, 2017)
Given the current climate change scenario, and its impact on a population of over six billion people. So, there is the need for climate understanding in the past, so the Início do Holocene period is great for the scientific community to have a greater understanding of the current climate. Initially it was thought that Início do Holocene period was a period of stable climate, with small evidence of abrupt climate change. Therefore, the general purpose of this study is to see if there was any modification in the cryosphere in the pre-industrial period (start 1850) in relation to the Início do Holocene period (about 11500 years ago), whose regions studied will be Antarctica and the Arctic, so we use the Hydrostatic model speedyCICE. We will make seasonal comparisons between the two periods, with the aim of checking which regions in Antarctica and the Arctic present the greatest differences between the periods studied. We analyze the variables: coverage of the sea ice, deposition of snow, snow thickness and the temperature of the ocean mixing layer. The speedy model is based on a dynamic nucleus, whose same is hydrostatic. In relation to vertical levels the speedy model has five layers in r coordinate, whose boundaries vary from 0, 0.15, 0.35, 0.65, 0.90, and 1. The speedy is coupled to the marine Ice model CICE (Los Alamos sea ice model), a model that represents marine ice conditions through the thermodynamics of the ocean related to the surface energy balance. The results point out that the Indian Ocean the Início do Holocene period presented the greatest differences between all the variables studied in the two periods addressed in the present work. This result also agrees with a period of lower heating of the ocean mixing layer in the region in the Início do Holocene. Dado o cenário atual de mudanças climáticas, e seu impacto em uma população com mais de seis bilhões de pessoas. Então, há a necessidade do entendimento do clima no passado, sendo assim, o período do Início do Holoceno possui informações ...